2022
DOI: 10.1111/1753-6405.13264
|View full text |Cite
|
Sign up to set email alerts
|

Women's perceptions of strategies to address the normalisation of gambling and gambling‐related harm

Abstract: Objective: Research has demonstrated that gambling is becoming increasingly normalised for women. As limited research has sought to understand women's perspectives on this issue, we sought women's opinions about the factors that may contribute to the normalisation of gambling for women, and the strategies that may counter this normalisation. Methods: Semi‐structured interviews were conducted with 41 women in young and middle adulthood, aged 20‐40 years. Results: Participants suggested that gambling was normal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 42 publications
1
6
0
Order By: Relevance
“…Finally, this study showed that in addition to reframing messages about gambling, people who have experienced gambling harm clearly support a range of strategies which are consistent with the public health approach to harm prevention. This aligns with previous evidence that gamblers also want governments to take legislative steps to restrict the gambling industry (Marko et al, 2022 ; McCarthy et al, 2022a ; Nyemcsok et al, 2022a ), as they have done alongside reframing messaging in other public health areas such as tobacco (Chapman and Freeman, 2008 ). In the Australian state of Victoria where many of the participants for this study resided, the Public Health and Wellbeing Act recognizes that governments have a “ a significant role in promoting and protecting the public health and wellbeing… [and] promoting conditions in which persons can be healthy” (Parliament of Victoria, 2008 :s4).…”
Section: Discussionsupporting
confidence: 85%
“…Finally, this study showed that in addition to reframing messages about gambling, people who have experienced gambling harm clearly support a range of strategies which are consistent with the public health approach to harm prevention. This aligns with previous evidence that gamblers also want governments to take legislative steps to restrict the gambling industry (Marko et al, 2022 ; McCarthy et al, 2022a ; Nyemcsok et al, 2022a ), as they have done alongside reframing messaging in other public health areas such as tobacco (Chapman and Freeman, 2008 ). In the Australian state of Victoria where many of the participants for this study resided, the Public Health and Wellbeing Act recognizes that governments have a “ a significant role in promoting and protecting the public health and wellbeing… [and] promoting conditions in which persons can be healthy” (Parliament of Victoria, 2008 :s4).…”
Section: Discussionsupporting
confidence: 85%
“…This research was part of a larger study investigating the normalisation of gambling for younger women in Australia. One other paper from this dataset has explored women's perceptions of strategies to address the normalisation of gambling 25 . The current study adopted a public health perspective and a critical qualitative approach to inquiry 26 .…”
Section: Methodsmentioning
confidence: 99%
“…One other paper from this dataset has explored women's perceptions of strategies to address the normalisation of gambling. 25 The current study adopted a public health perspective and a critical qualitative approach to inquiry. 26 The public health approach considers the broader impact of gambling beyond the individual, and focuses on external factors that may contribute to gambling‐related harm.…”
Section: Methodsmentioning
confidence: 99%
“…Framing is an active and dynamic process and different groups may frame issues in different ways based on their values, lived experiences and how they see the world. For example, while messages about the risks associated with the climate crisis can appeal to a sense of need for urgent action for some individuals ( Cammaerts, 2023 ; Arnot et al ., 2024 ), framing the climate crisis as a ‘climate emergency’ may also produce the opposite effect for others, wherein the word ‘emergency’ may demoralize and disempower citizens ( Hodder and Martin, 2009 ; Feldman and Hart, 2021 ). In relation to this study, the term ‘climate crisis’ has increasingly been used in place of ‘climate change’ to communicate the rising urgency and scope, and capture the systemic nature of the issue ( Kunelius and Roosvall, 2021 ).…”
Section: Introductionmentioning
confidence: 99%